2016
DOI: 10.21276/ijprhs.2016.05.09
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Arthritic and Anti-Microbial Effects of the Fruits of Grewia Subinaequalis D.C.

Abstract: Arthritis can be clearly say as an informal way of referring to joint pain and is most common among women, which occur frequently as people get older. Arthritis condition can also be defined as an auto immune disorder which is associated with pain and swelling 1. Generally arthritis is an inflammation of synovial joint due to immune mediated response. But the usage of antiinflammatory drugs in treating arthritis is not advisable all the times, because it does not suppress T-cell and B-cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…Further to this, Akhtar et al (2018) also postulated that 100 μg/ml of methanolic extract of phalsa can inhibit Staphylococcus aureus , Salmonella typhi , Enterobacter aerogens, and Bordetella bronchiseptica. While a study by Rajagopal et al (2016) reported that methanolic extract of phalsa fruit inhibited two bacterial strains (Escherichia coli and Lactobacillus acidophilus ). Additionally, the study identified that saponins, phenolic compounds, flavonoids, coumarins, and anthraquinones compounds present in the fruit were responsible for antibacterial action.…”
Section: Promising Health Benefits Of Grewia Asiaticamentioning
confidence: 99%
See 1 more Smart Citation
“…Further to this, Akhtar et al (2018) also postulated that 100 μg/ml of methanolic extract of phalsa can inhibit Staphylococcus aureus , Salmonella typhi , Enterobacter aerogens, and Bordetella bronchiseptica. While a study by Rajagopal et al (2016) reported that methanolic extract of phalsa fruit inhibited two bacterial strains (Escherichia coli and Lactobacillus acidophilus ). Additionally, the study identified that saponins, phenolic compounds, flavonoids, coumarins, and anthraquinones compounds present in the fruit were responsible for antibacterial action.…”
Section: Promising Health Benefits Of Grewia Asiaticamentioning
confidence: 99%
“…An in vitro study by Rajagopal et al (2016) reported that methanolic extract of phalsa fruit showed antiarthritic activity when compared to acetyl salicylic acid (aspirin); the authors measured this using the protein denaturation method. Another recent study, conducted by Babu et al (2017), reported that phalsa leaves were very effective in the treatment of urolithiasis.…”
Section: Promising Health Benefits Of Grewia Asiaticamentioning
confidence: 99%
“…Leaves: antimicrobial [44]; antiarthritic activity [45]; analgestic and anti-inflammatory activity [46]; antidiabetic [47].…”
Section: Urena Lobatamentioning
confidence: 99%
“…Daun dan batang widosari kaya akan sumber glikosida Resin yaitu digitata jalapin I. Widosari membantu menstabilkan berat badan, merangsang kontraksi miometrium pada saat nyeri persalinan, menambah berat badan, bersifat vasokonstriksi dan bronkokonstriksi, mengurangi tingkat Lipoprotein dan Lipid serta melindungi dari Infeksi Hati. Oleh karena itu, widosari berkhasiat sebagai agen hipoglikemik, antikonvulsi dan afrodisiaka (Rajagopal, P. L., Premaletha, K. & Sreejith, 2016;Rauniyar & Srivastava, 2020).…”
Section: Dd Widosariunclassified
“…Stimulan hormone laktogenik dari fungsi galactogogue tersebut yang mendukung khasiat dari widosari dalam memperbanyak produksi ASI. Aktivitas galagtogogue juga dapat meningkatkan kadar prolactin serum, protein dan glikogen pada kelenjar susu (Rajagopal, P. L., Premaletha, K. & Sreejith, 2016). .…”
Section: Dd Widosariunclassified